2012
DOI: 10.1155/2012/595427
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Frequency, Diagnostic Quality, and Cost of Lyme Borreliosis Testing in Germany: A Retrospective Model Analysis

Abstract: Background. Data on the economic impact of Lyme borreliosis (LB) on European health care systems is scarce. This project focused on the epidemiology and costs for laboratory testing in LB patients in Germany. Materials and Methods. We performed a sentinel analysis of epidemiological and medicoeconomic data for 2007 and 2008. Data was provided by a German statutory health insurance (DAK) company covering approx. 6.04 million members. In addition, the quality of diagnostic testing for LB in Germany was studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 36 publications
2
51
0
2
Order By: Relevance
“…In 2003, the total annual cost for LB in Scotland, a country with a low LB incidence, was still estimated as £331,000 (range £47,000-615,000) (Joss et al, 2003). In Germany, a study which combined retrospective investigations of proficiency testing surveys with a secondary analysis of claims data estimated costs of about 51.2 million Euro for diagnostics and treatment of LB outpatients (Müller et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2003, the total annual cost for LB in Scotland, a country with a low LB incidence, was still estimated as £331,000 (range £47,000-615,000) (Joss et al, 2003). In Germany, a study which combined retrospective investigations of proficiency testing surveys with a secondary analysis of claims data estimated costs of about 51.2 million Euro for diagnostics and treatment of LB outpatients (Müller et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of nationwide notification data it seems attractive to provisionally rely on other sources of data with comprehensive coverage such as hospital discharge data used in a recent study from France (Vandenesch et al, 2014) or claims data of health insurance companies. Following the latter approach, a study reported an average annual incidence of 261/100,000 for the diagnosis "LB" (Müller et al, 2012). These findings may point to an underestimation of the current impact of LB as a socioeconomic factor on the German health care system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy requires both a positive first-tier enzyme immunoassay (EIA) and a positive secondtier Western blot, yielding an overall specificity of 99.5% (13,14). Two-tiered testing has several limitations; specifically, it correctly identifies only 29 to 40% of patients presenting with an EM in the early stage of Lyme disease (10), and Western blot analysis is labor-intensive, subjective, and prone to issues with reproducibility (15)(16)(17).…”
mentioning
confidence: 99%
“…Bei 89% der Patienten fand sich ein Erythema migrans, bei 3% eine Neuroborreliose, bei 2% ein Lymphozytom, bei <1% eine Karditis, bei 5% eine Lyme-Arthritis, bei 1% eine Acrodermatitis chronica atrophicans und eine chronische Neuroborreliose in keinem Fall. Eine Studie, basierend auf Krankenkassendaten, geht von wenigsten 215.000 LymeBorelliose-Fällen/Jahr in Deutschland aus [17], während Daten der länderspe-zifischen Meldepflicht (östliche Bundesländer) maximal 30.000 Fälle in Deutschland erwarten lassen [18].…”
Section: Uukuniemi-virusunclassified